Application of Biofertilizers and Types of Planting Media on the Growth of Seedlings from True Shallot Seeds - Putra Utama; Risma Ayu Astuti; Abdul Hasyim Sodiq; Dewi Firnia (Agrotechnology Research Journal, 2024)
Superior seed quality is one of the keys to success in growing shallots. The purpose of this research was to analyze the effect of the concentration of biofertilizers and types of planting media on the growth of shallot seed origin of True Shallot Seeds (TSS) in the nursery. This research used a split-plot design consisting of two factors. The first factor is the concentration of biofertilizers, and the second factor is the type of planting medium. The results showed that the application of biofertilizers increased the growth of the shallot seed origin of TSS than without the application of biofertilizers. The application of biofertilizer at 1.5 mL.L-1 water gave the best results regarding the number of leaves per seedling and fresh weight. However, treatment with different concentrations of biofertilizers made no significant difference; treatment with concentrations of 1 mL.L-1 water was more efficient for the growth of shallot seeds. The type of planting media treatment did not significantly affect all parameters observed for the growth of shallot seed origin of TSS. There is an interaction between the concentration of biofertilizers and the type of planting media on the growth of shallot seed origin of TSS, namely the number of leaves aged 5 weeks after seedling, while for other parameters, there is no interaction between the concentration of biofertilizers and the type of planting medium on the growth of shallot seed origin of TSS.